2012
DOI: 10.1293/tox.25.45
|View full text |Cite
|
Sign up to set email alerts
|

Porencephaly in a Cynomolgus Monkey (<i>Macaca Fascicularis</i>)

Abstract: Porencephaly was observed in a female cynomolgus monkey ( Macaca fascicularis ) aged 5 years and 7 months. The cerebral hemisphere exhibited diffuse brownish excavation with partial defects of the full thickness of the hemispheric wall, and it constituted open channels between the lateral ventricular system and arachnoid space. In addition, the bilateral occipital lobe was slightly atrophied. Histopathologically, fibrous gliosis was spread out around the excavation area and its periphery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…In humans, main clinical signs include seizures, which are usually refractory to treatment, spastic paresis, and delayed cognitive development (Pokhraj et al, 2014). There is a report where a diagnosis of porencephaly was obtained based on tomographic findings in a new-born human patient (Pokhraj et al, 2014); however, most authors highlight the importance of macroscopic and histopathological analyses to better categorize the lesion and establish a definitive diagnosis (Hirowatari et al, 2012;Yamazaki et al, 2016). Magnetic resonance imaging is also indicated in these cases, and is considered the method of choice for detection of intracranial lesions (Mackillop, 2011;Schmidt et al, 2012;Hori et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, main clinical signs include seizures, which are usually refractory to treatment, spastic paresis, and delayed cognitive development (Pokhraj et al, 2014). There is a report where a diagnosis of porencephaly was obtained based on tomographic findings in a new-born human patient (Pokhraj et al, 2014); however, most authors highlight the importance of macroscopic and histopathological analyses to better categorize the lesion and establish a definitive diagnosis (Hirowatari et al, 2012;Yamazaki et al, 2016). Magnetic resonance imaging is also indicated in these cases, and is considered the method of choice for detection of intracranial lesions (Mackillop, 2011;Schmidt et al, 2012;Hori et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cystic intracranial malformations filled with cerebrospinal fluid (CSF) are occasionally reported in domestic animals and should be considered as a possible cause of seizures, blindness, ataxia, and other neurologic issues (Lee et al, 2009;Mackillop, 2011;Davies et al, 2012;Machado, 2012;Schmidt et al, 2012;Hori et al, 2015). Similar conditions are rarely described in wild animals, but there are reports of cerebral malformation with similar macroscopic characteristics in primates (Hirowatari et al, 2012) and a fennec fox (Yamazaki et al, 2016). Generally, cerebral malformations such as these are considered secondary to environmental factors, such as toxins or infections and vascular changes during the fetal period resulting in compromised brain perfusion and cortical tissue development (Greene et al, 1982;Sharp et al, 1999;Lee et al, 2009;Mackillop, 2011;Davies et al, 2012; http://dx.doi.org/10.1590/1678-4162-10986 L.V.L.…”
Section: Introduction mentioning
confidence: 99%
“…While the pathogenesis is uncertain, the constellation of histologic findings is suggestive of a chronic ischemic lesion, resulting from an ischemic event (thrombus of unknown origin) or traumatic injury causing impaired cerebral circulation. Due to the young age of affected animals, it has been suggested that the damage in some cases could occur in utero during development 280 , 281 . The change can rarely be associated with hydrocephalus and sometimes due to bacterial infection following direct CNS injections.…”
Section: Nervous Systemmentioning
confidence: 99%
“…In exotic animals, porecephaly is also rare, although a few cases have been reported in cynomolgous monkeys [7, 14]. Therefore, this article is the first to report a case of porencephaly in a fennec fox.…”
mentioning
confidence: 90%